No List of Political Assets The Collaboration of Iurii Olesha and Abram Room on "Strogii Iunosha" [A Strict Youth (1936)]. - Heil, Jerry T. (Slavistische Beitraege, 1989)
Iurii Olesha (1899-1960) was a relative late-comer to film work, if compared to several other important fictional prose writers oft he Soviet ,experimental' (modernist) 1920s. Olesha's first major filmscript (and his first script to be filmed) was "Strogii iunosha (A Strict Youth"), written in Odessa in 29 days in May und June 1934.